Transition from Slavery in Zanzibar and Mauritius - Sheriff, Abdul; Peerthum, Satyendra; Wahab, Saada Omar; Teelock, Vijaya (Book collections on Project MUSE., 2016)
This book presents a comparative history of slavery and the transition from slavery to free labour in Zanzibar and Mauritius, within the context of a wider comparative study of the subject in the Atlantic and Indian Ocean worlds. Both countries are islands, with roughly the same size of area and populations, a common colonial history, and both are multicultural societies. However, despite inhabiting and using the same oceanic space, there are differences in experiences and structures which deserve to be explored. In the nineteenth century, two types of slave systems developed on the islands--while Zanzibar represented a variant of an Indian Ocean slave system, Mauritius represented a variant of the Atlantic system--yet both flourished when the world was already under the hegemony of the global capitalist mode of production. This comparison, therefore, has to be seen in the context of their specific historical conjunctures and the types of slave systems in the overall theoretical conception of modes of production within which they manifested themselves, a concept that has become unfashionable but which is still essential. The starting point of many such efforts to compare slave systems has naturally been the much-studied slavery in the Atlantic region which has been used to provide a paradigm with which to study any type of slavery anywhere in the world. However, while Mauritian slavery was 100 per cent colonial slavery, slavery in Zanzibar has been described as 'Islamic slavery'. Both established plantation economies, although with different products, Zanzibar with cloves and Mauritius with sugar, and in both cases, the slaves faced a potential conflictual situation between former masters and slaves in the post-emancipation period. Another interesting focus in this book is the largely unresearched subject of female slaves. In Zanzibar, the privileged role of the suria whose status was defined by Sharia law was explored; and in Mauritius, the manumission of female slaves was explored as they formed the majority among manumitted slaves. The book will certainly prove helpful to those involved in comparing the Atlantic slave system with that of the Indian Ocean for the better understanding of both.